A cigar in the left hand, a paintbrush in the right: Illustration and the anatomical sciences. Issue 6 (4th April 2022) - Ferrigno, Christopher; Smith, Heather F.
Abstract: The anatomical sciences heavily rely on art and illustration to convey form, depth, and relationship within living structures. Today, biomedical illustrators carry forward traditions from 16th century artists through the likes of 20th century champions such as Frank Netter to help educators and researchers convey their messages to their listening, and more importantly, viewing audiences. Biomedical illustration programs are a valuable resource for academics to package their research as published figures, including graphical abstracts, in scientific journals. Here, we describe an innovative art‐science collaboration among The Anatomical Record, the Department of Anatomy and Cell Biology at Rush University, and the Master's Program in Biomedical Visualization at University of Illinois at Chicago, whose students were invited to create and submit scientific illustrations for consideration as cover art for the journal.